Konsep Nushuz dalam CLD KHI - Bihi, Kafa (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2017)
does not perform her duty to a husband. But it is not set about the husband’s nushuz as firmly as that of the wife. The Compilation of Islamic Law is considered unfair by gender activists so that the Gender Mainstreaming Working Group of the Department of Religion launched a script called Counter Legal Draft of Islamic Law Compilation (CLD-KHI). This paper examines CLD-KHI's offer of nushuz using the perspective of Islamic law, ie the views of some Muslim scholars about nushuz. Nushuz, as arranged in CLD KHI, applies to husband and wife. The settlement of nushuz is carried out by mean of peace, both by the wife and husband. The reason is because between the right and obligation of both are equal. The concept of nushuz in CLD-KHI is not in accordance with Islamic law, because nushuz is caused by one of the parties who does not perform the obligation or violate the rights of his/her partner. Of these rights and obligations, CLD KHI make them equal. While in Islamic Law, the rights and obligations of husband and wife are different. There is a difference between the provisions in Islamic law and CLD-KHI. In Islamic Law, the settlement of nushuz performed by a wife has three stages, they are advising, leaving in bed, and hitting with a punch that is not hard. While the effect of nushuz in CLD KHI is not clearly explained. [Dalam Kompilasi Hukum Islam, istilah nushuz bermakna istri yang tidak melakukan kewajibannya terhadap suami. Akan tetapi tidak diatur mengenai Nushuz suami secara tegas seperti pada istri. Kompilasi Hukum Islam dinilai kurang adil oleh para aktivis gender sehingga Kelompok Kerja Pengarusutamaan Gender Departemen Agama RI meluncurkan naskah yang disebut Counter Legal Draft Kompilasi Hukum Islam (CLD-KHI). Tulisan ini mengkaji tawaran CLD-KHI tentang nushuz dengan menggunakan perspektif hukum Islam, yaitu qaul fuqaha tentang nushuz. Nushuz yang diatur dalam CLD KHI berlaku bagi suami maupun istri. Penyelesaian Nushuz dilakukan dengan cara perdamaian, baik yang dilakukan oleh pihak istri maupun suami. Hal ini dikarenakan antara hak dan kewajiban keduanya setara. Konsep Nushuz dalam CLD KHI, tidak sesuai dengan hukum Islam, karena adanya Nushuz disebabkan oleh salah satu pihak yang tidak melaksanakan kewajiban atau melanggar hak pasangannya. Dari hak dan kewajiban inilah yang tidak sama, dalam CLD KHI mensetarakan keduanya, sedangkan dalam Hukum Islam hak dan kewajiban suami istri berbeda. Selanjutnya mengenai cara penyelesaian nushuz tidak sama. Dalam Hukum Islam penyelesaian Nushuz yang dilakukan oleh istri ada tiga tahap, yakni mulai menasehati, meninggalkan di tempat tidur, dan memukul dengan pukulan yang tidak keras Begitu juga dengan akibat Nushuz, dalam CLD KHI tidak dijelaskan.]